The Role of Ultrasound Compared to Biopsy of Temporal Arteries in the Diagnosis and Treatment of Giant Cell Arteritis (TABUL) : a diagnostic accuracy and cost-effectiveness study /: a diagnostic accuracy and cost-effectiveness study. (November 2016) - Luqmani, Raashid
No abstract available